Social Bonding and Youth Violence Prevention: A Criminological Examination of “Jogja Gelut Day” in Yogyakarta - Fuadi Isnawan (KRTHA BHAYANGKARA, 2026)
The emergence of street violence (klitih) in Yogyakarta illustrates the failure of traditional social control by parents and schools, causing teenagers to seek validation through deviant activities. The purpose of this study is to analyze the effectiveness of Jogja Gelut day as a non-penal means of preventing such street crime. The research method used is empirical research with a sociological approach to answer the research questions. This study provides an overview of criminological prevention to transform destructive adolescent behavior into prosocial activities that channel their energy. The results of this study show that JGD can reconstruct elements of social control by transforming street violence into a disciplined and structured sport. Through the training center before participating in JGD, coaches can provide facilities for the transition from involvement in filling free time to attachment to this positive figure. This process will foster an element of commitment to achievement and internalization of belief in legal norms. Therefore, the conclusion is that JGD is effective as a form of prevention based on social control in the community. The recommendation that can be given is for other local governments to create similar platforms that are tailored to the characteristics of the region so that many teenagers channel their energy into positive platforms and avoid criminal acts that will clearly harm themselves.